Quantum secure communication network architecture and mobile application solution - Jianquan WANG; Zhangchao MA; Xinzhong LI; Lei SUN; Changwei HU (Dianxin kexue)
As the first practical representative technology in the new quantum revolution,quantum key distribution (QKD) brings a promising solution to achieve long-term security guarantee,which has made series of progress from research to practical deployment and applications in recent years.The architecture design of quantum secure communication network was firstly discussed,which extended point-to-point QKD link to multi-user QKD network.Furthermore,combining with the classical cryptography,an enhanced solution was proposed to apply the quantum key generated by QKD to the mobile terminals,which offered the possibility to apply QKD in general mobile applications.